Reinstatement in Arbitration: The Grievors' Perspective - Williams, Kelly; Taras, Daphne Gottlieb (Relations industrielles / Industrial Relations, 2000)
Virtually absent in the arbitration literature is the voice of the grievor. Post-reinstatement experiences are examined primarily from the perspectives of a group of 7 Alberta grievors. First, a review is presented of the declining frequency of Alberta arbitrations, the extent to which dismissal cases form a proportion of the arbitral caseload, and the relatively low rate of reinstatement. Findings are: 1. Grievors are unaware of the public availability of arbitration awards. 2. Reinstated grievors are critical of the union that successfully defended them. 3. They have a more benign view of management. 4. Very little reinstatement assistance is offered. 5. Grievors' positive attitudes to their worksites are more determinative if successful reinstatement than remorse and acceptance of culpability.
Keywords: Arbitration; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Grievance procedures; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Wrongful discharge